Analysis of the Influence of Investment Value and Financial Technology on Economic Growth Through the Green Economy Index in Realizing Environmentally Friendly Infrastructure in Indonesia - Ahmaria, Siska; Fitriah, Aida; Yuliana, Indah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the influence of investment value and financial technology on economic growth through the green economy index in realizing environmentally friendly infrastructure in Indonesia. Using a quantitative approach with secondary data over the past 5 years, this study applies path analysis to test the causal relationship between variables. The results show that investment value and green economy have a significant positive effect on economic growth, while fintech does not have a significant effect on the green economy. The green economy is proven to mediate the relationship between investment value and economic growth, but does not mediate the effect of fintech on economic growth. These findings emphasize the importance of policies that integrate investment and green economy principles for sustainable growth